Rates, variability, and associated factors of polypharmacy in nursing home patients - Beloosesky Y (Dove Medical Press, 2013)
Yichayaou Beloosesky,1,3 Olga Nenaydenko,2 Revital Feige Gross Nevo,1,3 Abraham Adunsky,2,3 Avraham Weiss1,3 1Department of Geriatrics, Rabin Medical Center, Beilinson Hospital, Petah Tikva, 2Department of Geriatric Rehabilitation, Sheba Medical Center, Tel Hashomer, 3Sackler School of Medicine, Tel Aviv University, Petah Tikva, Israel Objectives: To determine the rate and variability of polypharmacy in nursing home (NH) residents and investigate its relationship to age, sex, functional status, length of stay, and comorbidities. Methods: We conducted a cross sectional, multicenter study that included six nursing homes. Demographic, clinical characteristics, Charlson comorbidity index (CCI), the number and classes of chronic medications, rate of polypharmacy >5 drugs (per day) and polypharmacy >7 drugs (per day) were recorded. Results: Nine hundred and ninety-three residents were included; 750 (75.5%) fully dependent residents and 243 (24.5%) mobile demented residents requiring institutional care. The mean age was 85.04±7.55 (65–108) years. The mean rates of polypharmacy >5 drugs and polypharmacy >7 drugs were 42.6% and 18.6%, respectively. Differences in polypharmacy >5 drugs and polypharmacy >7 drugs were observed in NHs 24.7%–56% and 4.9%–30.4%, respectively (P<0.001). Mean number of chronic drugs per resident was 5.14±2.60 from 3.81±2.24 to 5.95±2.73 (P<0.001). No differences in polypharmacy were found between sex and fully dependent versus mobile demented residents. The most common medications taken were for gastrointestinal, neurological, and cardiovascular disorders. Regression analysis revealed four independent variables for polypharmacy >5 drugs: groups aged 75–84 and >85 relative to 65–74, odds ratio (OR) 0.46 (95% confidence interval [CI] 0.27–0.78) P=0.004, OR 0.35 (95% confidence interval 0.19–0.53), respectively, P<0.001; length of stay >2 years, OR 0.51 (95% CI 0.36–0.73) P<0.001; CCI, OR 1.58 (95% CI 1.42–1.75) P<0.001; and feeding tube versus normal feeding, OR 0.27 (95% CI 0.12–0.60) P=0.001. Conclusion: Rates of polypharmacy in NHs are high with significant variability. Variability rates of polypharmacy, distinct residents' characteristics, and excessive use of certain drug groups may indicate that a decrease in medication is potentially feasible. Keywords: polypharmacy, nursing homes, variability, dementia, dependent, residents